Microparticles: Reliable Markers of Thrombosis - Chopra, Shelly (The Meducator, 2012)
Microparticles are vesicles that bud off cells in response to extracellular stimulation or apoptosis. They play an important role in the regulation of physiological and pathological pathways such as clot formation and the progression of thrombotic disease by influencing the expression of critical proteins and cofactors. The following Critical Review evaluates research findings on the potential significance of microparticles as indicators of thrombotic risk.